A Proposed Algorithm for Endoscopic Ultrasound-Guided Rendezvous Technique in Failed Biliary Cannulation - Matsubara, Saburo; Nakagawa, Keito; Suda, Kentaro; Otsuka, Takeshi; Isayama, Hiroyuki; Nakai, Yousuke; Oka, Masashi; Nagoshi, Sumiko (Journal of clinical medicine, 2020)
Background: The selection of an approach route in endoscopic ultrasound-guided rendezvous (EUS-RV) for failed biliary cannulation is complicated. We proposed an algorithm for EUS-RV. Methods: We retrospectively evaluated consecutive EUS-RV cases between April 2017 and July 2020. Puncturing the distal extrahepatic bile duct (EHBD) from the duodenal second part (D2) (DEHBD/D2 route) was attempted first. If necessary, puncturing the proximal EHBD from the duodenal bulb (D1) (PEHBD/D1 route), puncturing the left intrahepatic bile duct (IHBD) from the stomach (LIHBD/S route), or puncturing the right IHBD from the D1 (RIHBD/D1 route) were attempted in this order. Results: A total of 16 patients were included. The DEHBD/D2 route was used in 10 (62.5%) patients. The PEHBD/D1 route was attempted in five (31.3%) patients, and the biliary puncture failed in one patient in whom the RIHBD/D1 route was used because of tumor invasion to the left hepatic lobe. The LIHBD/S route was applied in one (6.3%) patient. Successful biliary cannulation was achieved in all patients eventually. The time from the puncture to the guidewire placement in the DEHBD/D2 route (3.5 min) was shorter than that in other methods (14.0 min) (p = 0.014). Adverse events occurred in one (6.3%) patient with moderate pancreatitis. Conclusions: The proposed algorithm might be useful for the selection of an appropriate approach route in EUS-RV.